Efficiency and Effectiveness: Enterprise Architecture Strategies for Healthcare Service - Alwi, Muchamad Nurdin; Hindarto, Djarot; Marina, Anna; Yudhakusuma, Dudi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
In a globally evolving health landscape, attaining maximum efficiency and efficacy is of the utmost importance. The present study investigates the utilization of Enterprise Architecture tactics to enhance healthcare services, specifically by streamlining operations and boosting overall effectiveness. Through an examination of organizational processes, patient care, information management, and healthcare delivery, this study sheds light on the transformative potential of EA as a framework. This research investigates the strategic alignment of health systems through the application of EA principles to establish an infrastructure that is both harmonious and interoperable. The present study investigates the significance of digital transformation within the healthcare sector, with a particular focus on the ways in which EA strategies can enable the smooth incorporation of technological advancements to enhance patient outcomes. This study emphasizes the need for patient-specific health systems. It highlights the significance of a patient-centered approach in the context of EA. By conducting an exhaustive examination of the implementation of EA in the healthcare sector, this study intends to provide organizations with direction on how to enhance their service provision. Empirical evidence indicates that by utilizing EA to harmonize business objectives, technological progress, and patient-centric methodologies, significant enhancements in efficiency and efficacy can be achieved, thereby culminating in elevated benchmarks of healthcare provision. In conclusion, the study urges the extensive implementation of EA strategies within health systems, acknowledging its capacity to transform service frameworks and foster a health ecosystem that is more attentive to patients and proactive.